If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 2p = 6p + -20 Reorder the terms: 4 + 2p = -20 + 6p Solving 4 + 2p = -20 + 6p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6p' to each side of the equation. 4 + 2p + -6p = -20 + 6p + -6p Combine like terms: 2p + -6p = -4p 4 + -4p = -20 + 6p + -6p Combine like terms: 6p + -6p = 0 4 + -4p = -20 + 0 4 + -4p = -20 Add '-4' to each side of the equation. 4 + -4 + -4p = -20 + -4 Combine like terms: 4 + -4 = 0 0 + -4p = -20 + -4 -4p = -20 + -4 Combine like terms: -20 + -4 = -24 -4p = -24 Divide each side by '-4'. p = 6 Simplifying p = 6
| 75x+35x-10=0 | | 5p+6-2p-4=17 | | 0.0001x+2=4x+2 | | 7(x-4)-4x=2x-3-(5-6x) | | 1234x+2=4x-99 | | 4(x-5)=(5-x)4 | | (2v)-4=8 | | 2c-16=10c | | 24x+2=4x+-8 | | b^2=8b-22 | | 9x+2=4x+0.1 | | 2.3-5y=-37 | | X(n+3)=3n+9 | | -log(x)=7.5 | | X(n+3)=3n+8 | | 45x-16=-20x+116 | | 1x+2=4x+3 | | x^3+x^2+9x-19=0 | | 36X+36Y+6K= | | 9x-15=3x-13 | | 7-(-x+1)=9x+6 | | -4x=8x-3 | | 17+x-15=-9 | | 9x-15=5x-13 | | -6+3y=12 | | -13=2x-4x+3 | | 5(1-4)=3(1+2) | | 5x-80=2x-11 | | y=-12x+24 | | 50x+2y=50 | | 0.16b=-12 | | -16=3x-5x-2 |